Synthesis of Technical Carboxymethyl Cellulose with Increased Content of the Main Substance - M.K. Urozov; M.G. Djurayev; A.X. Raximov; B.B. Ochildiyev (International Journal on Orange Technologies, 2021)
It is known that a conventional cellulose ether Mecca CMC wide application in various industries, including the construction industry. CMC has a viscosity of the water used for the construction sector, heat tolerance positive.